2013
DOI: 10.1002/aic.14190
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of oscillation of axisymmetric turbulent opposed jets with modulated airflow

Abstract: Oscillation behaviors of axisymmetric opposed jets with modulated airflow were experimentally studied. The oscillation frequency, the oscillation amplitude, and the movement velocity of the impingement plane at various nozzle separations, excitation frequencies, and exit turbulence intensities have been investigated by a hot-wire anemometer and flow visualization technique combined with a high-speed camera. Results show that the oscillation frequency of the impingement plane is nearly equal to the excitation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…The flapping oscillation amplitude of impingement plane increases with excitation amplitude both in Reactors I and II, which is consistent with the results of axial oscillation in round opposed jets (Li et al, 2013a) and horizontal oscillation in planar opposed jets with excitation (Li et al, 2013b). The flapping amplitude decreases with the increase of excitation frequencies in Reactor I, but it will reach peak value at a certain excitation frequency in Reactor II, which has not been reported in other studies.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The flapping oscillation amplitude of impingement plane increases with excitation amplitude both in Reactors I and II, which is consistent with the results of axial oscillation in round opposed jets (Li et al, 2013a) and horizontal oscillation in planar opposed jets with excitation (Li et al, 2013b). The flapping amplitude decreases with the increase of excitation frequencies in Reactor I, but it will reach peak value at a certain excitation frequency in Reactor II, which has not been reported in other studies.…”
Section: Resultssupporting
confidence: 93%
“…Current results indicate that the excited oscillation is caused by the pulsed inflow and its frequency is determined by the excitation frequency, which can be explained similarly to our previous work (Li et al, 2013a). Conclusions in the study reveal that the difference of instantaneous velocities caused by pulsed inflow will result in the movement of the impingement plane, and the oscillation frequency will synchronize with the excitation frequency.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…As for the axisymmetric opposed jets, multiple steady states of impinging plane in closely spaced axisymmetric opposed jets have been found by experimental way [6,7] and numerical way [3]. Li et al [4,8,9] experimentally studied the dynamic behavior of the impinging plane and found the phenomena of axial quasi-periodic oscillation of impinging plane and stagnation point offsets when L/D varied. The complex turbulent characteristic in impinging zone has also been widely studied [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 95%